Non-rigid image registration using a modified fuzzy feature-based inference system for 3D cardiac motion estimation. (June 2021) - Hosseini, Monire Sheikh; Moradi, Mahammad Hassan; Tabassian, Mahdi; D'hooge, Jan
Highlights: Describing spatial properties of the 3D TTE images based on the scale-invariant feature transform (SIFT) descriptor. Registering 3D TTE images through fuzzy rule-based system. Estimation non-rigid cardiac motion by interpretable fuzzy rules. Achieving comparable result with well-known commercial cardiac motion estimation methods. Abstract: Background and objective: Non-rigid image registration is a well-established method for estimating cardiac motion on 3D echocardiographic images. However, such images have relatively poor spatio-temporal resolution making registration challenging. Some of the main challenges are extracting features relevant to the registration problem and defining a suitable geometrical transformation to be applied. The latter can be tackled using a fuzzy inference system considering its potential in transformation modeling. From this point of view, feature-based image registration can be considered an identification problem in which the transformation parameters are computed through an optimization process. This study, thus, aims to estimate cardiac motion on 3D echocardiographic images based on feature-based non-rigid image registration through sets of modified fuzzy rules. Methods: The 3D volume features were extracted with the popular scale-invariant feature transform (SIFT) descriptors in 3D space. Sets of fuzzy rules were generated according to the extracted features to register every two consecutive frames. Finally, some supplementary rules modified the registration rule for estimating cardiac motion. Results: Applying the fuzzy feature-based inference system on the STRAUS synthetic database showed the proposed method to be competitive with other well-established registration algorithms in terms of tracking error and accuracy of strain estimates. The proposed algorithm yielded a tracking error of 1 mm and a relative circumferential strain error of 0.82±4.69%. In addition, the potential of the proposed algorithm for clinical applications was confirmed by evaluating its performance on an in-vivo database called CETUS. Conclusion: This paper proposes a novel registration method based on fuzzy logic which was shown to enable tracking complex cardiac deformations in 3D echocardiographic images with high accuracy.